The Awareness of Violence Reporting System Among Healthcare Providers and the Impact of New Ministry of Health Violence Penalties in Saudi Arabia - Towhari AA; Bugis BA (Dove Medical Press, 2020)
Aisha A Towhari,1,2 Bussma A Bugis3 1Respiratory Care Department, Prince Sultan Military College of Health Sciences, Al-Dhahran, Kingdom of Saudi Arabia; 2Department of Public Health, College of Health Sciences, Saudi Electronic University, Riyadh, Kingdom of Saudi Arabia; 3Department of Public Health, College of Health Sciences, Saudi Electronic University, Dammam, Kingdom of Saudi ArabiaCorrespondence: Aisha A Towhari Respiratory Care Department, Prince Sultan Military College of Health Sciences, Dhahran P.O. Box 946, 31932, Saudi ArabiaTel +966 13 8440000, EXT: 3603 Email Atowhari@psmchs.edu.saPurpose: Healthcare professionals are one of the most vulnerable groups subjected to verbal and physical violence daily while carrying out their duties; such violence is a worldwide concern. This study aimed to explore the awareness of a violence reporting system among healthcare providers and the impact of the new Ministry of Health (MOH) violence regulations at one of the Eastern Region hospitals in Saudi Arabia.Methods: A cross-sectional study was conducted from January to February 2020. The study included 210 healthcare providers from different specialties working in critical care units. A sample of 137 healthcare providers was selected randomly, and a self-administered questionnaire was distributed accordingly.Results: In this study, 31.4% of participants were not aware of whether they had a specific system for reporting violent incidents, while 68.6% had no training on these systems. Experiences of violence among the staff decreased from 78.6% before the MOH regulations to almost 20% after the MOH regulations.Conclusion: The majority of victims did not report incidents because there is a lack of system privacy, and the workers felt that the incidents of violence were a part of their daily jobs. In addition, this study revealed that the majority of healthcare workers did not receive training on the reporting system, which explains their lack of knowledge about the formal reporting system. Finally, the MOH initiative and penalties for controlling workplace violence have resulted in a significant drop in the prevalence of violence among healthcare workers.Keywords: Saudi Arabia, violence penalties, Ministry of Health, reporting of violence, healthcare workers